Warsztaty techniczno-przyrodnicze a kształcenie kompetencji społecznych studentów – przyszłych nauczycieli i uczniów szkół podstawowych - Czerwiec, Karolina; Staśko, Renata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Szeroki zakres kompetencji społecznych nauczyciela pozwala mu na wywieranie wpływu na uczniów w różnego rodzaju sytuacjach społecznych. Powstawanie i rozwijanie się kompetencji możliwe jest dzięki zdolności przetwarzania informacji behawioralnych – tzw. inteligencji społecznej [Argyle 1994]. Natomiast realizowane podczas pozalekcyjnych zajęć aktywności dają uczniom większą swobodę w samodzielnym poszukiwaniu rozwiązań, projektowaniu działań i odpowiadaniu na problematyczne kwestie bez angażowania nauczyciela w podawanie gotowych odpowiedzi i rozwiązań. Celem badań było podniesienie poziomu kompetencji społecznych studentów i uczniów szkół podstawowych poprzez uczestnictwo w interdyscyplinarnych warsztatach edukacyjnych. Wykazano, że uczestnicy badań dostrzegają konieczność organizowania tego typu zajęć w celu kształtowania odpowiedniego podejścia do współczesnych problemów naukowych i cywilizacyjnych.

A wide field of teacher's social competencies allows to influence the pupils in different kinds of social situations. Creating and development of competencies is possible through the ability of information behavioral process – so-called social intelligence [Argyle 1994]. While, extra-curricular activities give pupils freedom in independent searching of solutions, design activities and responding to problematic issues without teacher commitment in the giving of finished answers and solutions. The aim of the research was to raise the level of social competencies of the students and the primary school pupils through participation in the interdisciplinary educational workshops. The results showed that participants of the research recognize the need to organize such activities – in their opinion it's important in shaping an appropriate approach to the contemporary science and civilization problems.
Technical and science workshops – training of social competencies of students – future teachers and primary school pupils
Keywords: edukacja techniczna i przyrodnicza; interdyscyplinarność; kompetencje społeczne; warsztaty; technical and science education; interdisciplinarity; social competencies; workshops